Pro-p subgroups of profinite completions of 3-manifold groups - Wilton, HJR; Zalesskii, P (Wiley, 2017)
We completely describe the finitely generated pro-$p$ subgroups of the profinite completion of the fundamental group of an arbitrary 3-manifold. We also prove a pro-$p$ analogue of the main theorem of Bass–Serre theory for finitely generated pro-$p$ groups.
Keywords: math.GR; math.GR; math.GT